The determinants of FDI inflow in manufacturing sector of Malaysia - Fakhredin, Farzad; Nezakati, Hossein *; Vaighan, Behzad Mahmoudi (2010)
The role of foreign direct investment (FDI) to create competition, technology transfer, reducing unemployment and generating productive economic growth is undeniable. Therefore, policy makers and economists seek to identify the factors that affect FDI in different sectors. Accordingly, this study investigates the determinants of FDI in manufacturing sector of Malaysia over 2000- 2009. Using quarterly data we find a and significant effect of domestic credit to private sector provided by banking system and development expenditure of government in this sector. Meanwhile, the effect of 2007- recession on FDI inflow of Malaysia is positive and significant, though due this recession reduction of the world aggregate FDI reduced the growth of FDI inflow of manufacturing sector of Malaysia. The effect of corruption on FDI's growth is also negative and significant.